THE EVALUATION AND TREATMENT OF HEMORRHOIDS: AN UPDATED SYSTEMATIC REVIEW - Suryadi, Rokhim; Supriyo, Bambang; Yulanda Putra, Yosie; Auliya, Ahsan; Hardiyansah, M. Yudhi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Hemorrhoids are naturally occurring veins in the lower rectum and anus that aid in continence. The severity of pain or discomfort associated with hemorrhoids is influenced by factors such as their size, thrombosis, and location relative to the dentate line. During the history-taking and physical examination, it's crucial to identify risk factors and clinical signs that may suggest more serious underlying conditions.The objective of this study is to conduct an extensive systematic review involving the evaluation and treatment of hemorrhoids based on literature published within the past decade. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2014 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, and SpringerLink. Result: A total of 1,097 articles s were retrieved from online databases (PubMed, SagePub, and SpringerLink). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Hemorrhoids require proper diagnosis and management. Pregnancy and inflammation increases the risk of hemorrhoids. Conservative treatments work for mild cases, while surgery may be needed for severe ones. Theres an association between hemorrhoids and colorectal cancer, prompting screening recommendations for patients.